Simulation of triple-diffusive Carreau fluid transport with sodium chloride and sucrose via MATLAB bvp4c - Balakrishnan, Nanthini; Parvin, Shahanaz; Jamshed, Wasim; Hussain, Syed M.; Ibrahim, Rabha W.; Mohamed Isa, Siti Suzilliana Putri (John Wiley and Sons Inc, 2026)
Triple diffusive convection (or triple diffusion) arises in fluid systems, where three different scalar gradients (typically heat, solute 1, and solute 2) drive buoyancy and interact with each other through diffusion. Triple diffusive can be observed in the biomedicine field, such as dialysis and blood perfusion. Motivated by the development of triple diffusion, therefore, a mathematical model of 2D triple diffusive boundary layer flow (BLF) of Carreau fluid induced by an inclined compressing plate is developed. The sodium chloride (NaCl) and sucrose (C12H22O11) are assumed to be submerged into Carreau fluid to form triple diffusive flow with the occurrence of a temperature gradient. Regulating variables, such as buoyancy rate, radiation, and thermophoresis factors make up the suggested model. Furthermore, the present framework has been influenced by the variety of these numbers: Schmidt, Soret, and Dufour. First, the motion, thermal property, and mass property of NaCl-C12H22O11/Carreau fluid are combined into a partial differential equations (PDEs) to represent the mathematical model. These partition numbers will next be transformed into ordinary differential equations (ODEs). Final ODEs are solved numerically using a solver known as bvp4c in the MATLAB software. The velocity increment is affected by the buoyancy ratio parameters for sodium chloride and sucrose. All the thermal parameters are found to enhance the temperature profile. The physical parameters related to the flow variation (skin friction coefficient) increase when the opposing buoyancy ratio parameter increases. The Dufour number owned by the sucrose molecule causes the local Nusselt number to be increase. For each NaCl and C12H22O11, the local Sherwood numbers decrease due to the increasing Soret number.